Analysis of Management of Lithuanian Companies Lising European Business Excellence Model - Mikulis, Juozas; Kaziliūnas, Adolfas (Ekonomika, 2001)
The research was conducted using EFQM (European Foundation for Quality) Excellence Model in order to analyze the usage of Total Quality Management principles, trends and prospectives in Lithuanian business management. The results of the analysis revealed that the worst managed interested party of Lithuanian organizations is employees. Management of large companies meet more European Business Excellence Models requirements than medium and small organizations. The results of evaluation among all categories of companies increased from 1998 to 1999 but no Significant further improvement was detected. Lithuanian companies still have lots of potential of increasing its competitiveness by integrating TQM in management process more effectively. However ISO 9000 certification covers some of TQM principles which are mostly used in Lithuanian companies. New edition of and further popularization of standard among Lithuanian exporters will decrease the gap between Lithuanian organizations management practices and Business Excellence Model.